A continental‐scale analysis of feral cat diet in Australia. (2nd February 2015) - Doherty, Tim S.; Davis, Robert A.; van Etten, Eddie J. B.; Algar, Dave; Collier, Neil; Dickman, Chris R.; Edwards, Glenn; Masters, Pip; Palmer, Russell; Robinson, Sue; McGeoch, Melodie
Abstract Aim Reducing the impacts of feral cats (Felis catus) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species' ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats' diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.